High-Fructose Diet Increases Renal ChREBPβ Expression, Leading to Intrarenal Fat Accumulation in a Rat Model with Metabolic Syndrome - Ariel Bier; Eliyahu Shapira; Rawan Khasbab; Yehonatan Sharabi; Ehud Grossman; Avshalom Leibowitz (Biology, 2022)
Fructose consumption is associated with metabolic syndrome (MeS). Dysregulated lipid metabolism and ectopic lipid accumulation, such as in “fatty liver’’, are pivotal components of the syndrome. MeS is also associated with chronic kidney disease (CKD). The aim of this study was to evaluate kidney fructose metabolism and whether the addition of fructose leads to intrarenal fat accumulation. Sprague Dawley rats were fed either normal chow (Ctrl) or a high-fructose diet (HFrD). MeS features such as blood pressure and metabolic parameters in blood were measured. The kidneys were harvested for ChREBPβ and de novo lipogenesis (DNL) gene expression, triglyceride content and histopathology staining. HK2 (human kidney) cells were treated with fructose for 48 h and gene expression for ChREBPβ and DNL were determined. The HFrD rats exhibited higher blood pressure, glucose and triglyceride levels. The kidney weight of the HFrD rats was significantly higher than Ctrl rats. The difference can be explained by the higher triglyceride content in the HFrD kidneys. Oil red staining revealed lipid droplet formation in the HFrD kidneys, which was also supported by increased adipophilin mRNA expression. For ChREBPβ and its downstream genes, scd and fasn, mRNA expression was elevated in the HFrD kidneys. Treating HK2 cells with 40 mM fructose increased the expression of ChREBPβ. This study demonstrates that fructose consumption leads to intrarenal lipid accumulation and to the formation of a “fatty kidney”. This suggests a potential mechanism that can at least partially explain CKD development in fructose-induced MeS.